Encryption based on reversible cellular automata - PING Ping; ZHOU Yao; ZHANG Hong; LIU Feng-yu (Tongxin xuebao)
The reversible cellular automata is featured by its no information loss and parallel information processing. A new block cipher based on reversible second-order toggle cellular automata was proposed. Instead of using the whole rules space as the keys space,the new algorithm introduces a parameter λ to partition the rules space and proves that rules with λ=0.5 are becoming to encrypt. Compared with the general irreversible toggle cellular automata cryptosystem,the proposed method greatly improves the speed of encryption and has large keys space,it can resist bruce attack and differ-ential cryptanalysis.